Morphine-induced modulation of Nrf2-antioxidant response element signaling pathway in primary human brain microvascular endothelial cells - Sandrine Reymond; Tatjana Vujić; Domitille Schvartz; Jean-Charles Sanchez (Scientific Reports, 2022)
Abstract Morphine is one of the most potent opioid analgesic used for pain treatment. Morphine action in the central nervous system requires crossing the blood–brain barrier. Due to the controversial relationship between morphine and oxidative stress, the potential pro- or antioxidant effects of morphine in the blood–brain barrier is important to be understood, as oxidative stress could cause its disruption and predispose to neurodegenerative diseases. However, investigation is scarce in human brain endothelial cells. Therefore, the present study evaluated the impact of morphine exposure at three different concentrations (1, 10 and 100 µM) for 24 h and 48 h on primary human brain microvascular endothelial cells. A quantitative data-independent acquisition mass spectrometry strategy was used to analyze proteome modulations. Almost 3000 proteins were quantified of which 217 were reported to be significantly regulated in at least one condition versus untreated control. Pathway enrichment analysis unveiled dysregulation of the Nrf2 pathway involved in oxidative stress response. Seahorse assay underlined mitochondria dysfunctions, which were supported by significant expression modulations of relevant mitochondrial proteins. In conclusion, our study revealed the dysregulation of the Nrf2 pathway and mitochondria dysfunctions after morphine exposure, highlighting a potential redox imbalance in human brain endothelial cells.